Bioinformatics analysis combined with experimental validation reveals the novel mechanisms of multi-targets of dapagliflozin attenuating diabetic liver injury - Wang, Pengyu; Sun, Zhen; Lan, Qing; Zhang, Shuo; Song, Yan; Yang, Leiming; Chen, Mi; Shen, Jianfen; Huang, Qi; Zhang, Youzhi (Frontiers in Endocrinology, 2025)
ObjectiveDiabetic liver injury, a chronic complication of diabetes mellitus (DM), has been extensively documented. Dapagliflozin, a sodium-glucose co-transporter 2 (SGLT2) inhibitor, has shown significant therapeutic benefits in clinical trials for the management of diabetes However, the specific mechanism on the treatment of diabetic liver injury with dapagliflozin is not fully understood. Therefore, this study aims to further explore the potential mechanism of dapagliflozin on diabetic liver injury based on bioinformatics analysis and experimental verification.MethodsDiabetic liver injury was induced by a high-fat diet combined with STZ in mice. Biochemical kit detection and H&E staining were used to observe lipid aggregation and oxidative stress in liver tissue. Moreover, the expression of inflammatory and apoptosis-related factors was detected using western blotting (WB) and quantitative polymerase chain reaction (qPCR). Subsequently, differential expressions genes analysis, weighted gene co-expression network analysis (WGCNA), molecular docking, as well as molecular dynamics was conducted based on the Gene Expression Omnibus (GEO) and pharmacology databases. Finally, WB and qPCR were performed to validate the mechanism of dapagliflozin on diabetic liver injury in vivo and in vitro.ResultsDapagliflozin alleviated diabetic liver injury by decreasing lipid deposition, oxidative stress levels, the inflammatary and apoptosis-related proteins and mRNA levels, while it also reducing blood glucose. Mechanically, 78 overlapping genes of dapagliflozin and diabetic liver injury were obtained. Notably, Mapk3, Mapk1, Ikbkb, and Nfkb1 as the hub genes involved in dapagliflozin attenuating diabetic liver injury were identified, and dapagliflozin exhibited better affinity with these proteins. Moreover, dapagliflozin inhibited the elevated protein (genes) levels of ERK1/2 (Mapk3, Mapk1), IKKβ(Ikbkb), and NF-κB (Nfkb1), which are induced by diabetic liver injury, as confirmed by both in vivo and in vitro experiments.ConclusionDapagliflozin ameliorated diabetic liver injury by inhibiting the ERK/IKKβ/NF-κB signalling pathway, as demonstrated by bioinformatics analysis combined with in vivo and in vitro experiments.